Allergy and Respiration - Pokorski, Mieczyslaw (Neuroscience and Respiration, 2016)
Allergy is an increasing health issue. It often targets the respiratory tract and entwines with respiratory ailments, which makes it difficult to discern the cause-effect linkage. Nonetheless, measures to counter the allergic background are a linchpin in preserving respiratory health. This book is an update on current advances in clinical and basic science on allergy and related topics. The diagnostics of allergy requires a multidisciplinary approach, including molecular examinations aimed at unraveling the intracellular control cascades. Chapters give insight into the innovations concerning modern pulmonary function tests, discuss pharmacological paradigms, and tackle the overlapping infectious aspects and clinical symptoms and markers. Environmental and genetic factors elicit a spectrum of inflammatory phenotypes linked to differential body responses to allergic perturbations. The book is intended for healthcare professionals, notably pulmonologists, primary care physicians, and medical researchers. .